Neurokinin-1 antagonist orvepitant for EGFRI-induced pruritus in patients with cancer: a randomised, placebo-controlled phase II trial. Issue 2 (6th February 2020) - Vincenzi, Bruno; Trower, Mike; Duggal, Ajay; Guglielmini, Pamela; Harris, Peter; Jackson, David; Lacouture, Mario E; Ratti, Emiliangelo; Tonini, Giuseppe; Wood, Andrew; Ständer, Sonja
Abstract : Objective: To evaluate the efficacy of orvepitant (10 or 30 mg given once daily, orally for 4 weeks), a neurokinin-1 receptor antagonist, compared with placebo in reducing the intensity of epidermal growth factor receptor inhibitor (EGFRI)-induced intense pruritus. Design: Randomised, double-blind, placebo-controlled clinical trial. Setting: 15 hospitals in Italy and five hospitals in the UK. Participants: 44 patients aged ≥18 years receiving an EGFRI for a histologically confirmed malignant solid tumour and experiencing moderate or intense pruritus after EGFRI treatment. Intervention: 30 or 10 mg orvepitant or placebo tablets once daily for 4 weeks (randomised 1:1:1). Primary and secondary outcome measures: The primary endpoint was change from baseline in mean patient-recorded numerical rating scale (NRS) score (over the last three recordings) at week 4. Secondary outcome measures were NRS score, verbal rating scale score, Skindex-16 and Leeds Sleep Evaluation Questionnaire at each study visit (baseline, weeks 1, 4, 8); rescue medication use; EGFRI dose reduction; and study withdrawal because of intense uncontrolled pruritus. Results: The trial was terminated early because of recruitment challenges; only 44 of the planned 90 patients were randomised. All patients were analysed for efficacy and safety. Mean NRS score change from baseline to week 4 was −2.78 (SD: 2.64) points in the 30 mg group, −3.04 (SD: 3.06) points in the 10 mg group and −3.21 (SD: 1.77) points in the placebo group; the difference between orvepitant and placebo was not statistically significant. No safety signal was detected. Adverse events related to orvepitant (asthenia, dizziness, dry mouth, hyperhidrosis) were all of mild or moderate severity. Conclusions: Orvepitant was safe and well tolerated. No difference in NRS score between the orvepitant and placebo groups was observed at the week 4 primary endpoint. A number of explanations for this outcome are possible. Trial registration number: EudraCT2013-002763-25.